To be continued

Calculus Level 3

2 + 1 0 + 1 1 + 1 8 + 1 2 + 1 0 + 1 1 + 1 8 + = a + b c \Large 2+\frac{1}{0+\frac{1}{1+\frac{1}{8+\frac{1}{2+\frac{1}{0+\frac{1}{1+\frac{1}{8+\cdot_{\cdot_{\cdot}}}}}}}}}= \frac{a+\sqrt{b}}{c}

Submit b c a \dfrac{bc}{a} , where a a , b b , and c c are positive integers with b b square-free.


The answer is 28.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Let x x be the given number. Then

x = 2 + 1 0 + 1 1 + 1 8 + 1 x = 2 + 1 0 + 1 1 + x 8 x + 1 \large \begin{aligned} x & = 2 + \frac 1{0+\frac 1{1+\frac 1{8+\frac 1x}}} \\ & = 2 + \frac 1{0+\frac 1{1+\frac x{8x+1}}} \end{aligned}

= 2 + 1 0 + 8 x + 1 9 x + 1 = 2 + 9 x + 1 8 x + 1 = 25 x + 3 8 x + 1 \begin{aligned} \ \ \ & = 2 + \frac 1{0+\frac {8x+1}{9x+1}} \\ & = 2 + \frac {9x+1}{8x+1} \\ & = \frac {25x+3}{8x+1} \end{aligned}

x ( 8 x + 1 ) = 25 x + 3 8 x 2 24 x 3 = 0 x = 24 + 2 4 2 4 ( 8 ) ( 3 ) 2 × 8 Note that x > 0 = 6 + 42 4 \begin{aligned} \implies x(8x+1) & = 25x+3 \\ 8x^2 - 24x - 3 & = 0 \\ \implies x & = \frac {24 + \sqrt{24^2-4(8)(-3)}}{2\times 8} & \small \color{#3D99F6} \text{Note that }x > 0 \\ & = \frac {6+\sqrt{42}}4 \end{aligned}

Therefore, b c a = 42 × 4 6 = 28 \dfrac {bc}a = \dfrac {42\times 4}6 = \boxed{28} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...